Anatomical Influences on Electrical Impedance Tomography: Bioimpedances in Cardiac Radiofrequency Ablation - Minh Duc, Nguyen; Anh Huyen, Ngo; Minh Thao, Hoang; Phuong Linh, Nguyen; Qian, Pierre (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2, 2025)
Electrical Impedance Tomography (EIT) can potentially improve cardiac radiofrequency ablation’s efficacy in treating arrhythmias, as proven in simulations and in vivo experiments. However, a proper EIT model for measuring ablation lesions is still absent without access to patients’ CT scans in practice. This study explored the anatomical structure’s influences on EIT bioimpedances to provide guidance on which organs are required for an EIT ablation model. Ablations and 64-channel bioimpedances were simulated using a realistic thoracic model built from open-source CT scans. Multiple ablation conditions and catheter locations were generated to obtain a diverse set of lesions. EIT bioimpedances were simulated under different model conditions, ranging from the simplest model containing only the heart and lungs to the full model including most major thoracic and abdominal organs. Tukey’s HSD tests and differences in EIT bioimpedances were conducted to evaluate the contribution of each organ to the lesion impedances. The results showed that the thoracic bones were heavily influential and could overshadow other organs’ effects. However, the inclusion of both abdominal organs and scapulae could produce a similar effect when the thoracic bones were absent. Therefore, one could choose to include either thoracic bones or abdominal organs and scapulae in the EIT model, not necessarily together, aside from the heart and lungs for lesion ablation imaging. Further in vivo experiments are required to test these results.